Cryptic female choice via sperm dumping favours male copulatory courtship in a spider - Peretti, Alfredo Vicente (2010)
Males of many animals perform 'copulatory courtship' during copulation, but the possible reproductive significance of this behaviour has seldom been investigated. In some animals, including the spider Physocyclus globosus (Pholcidae), the female discards sperm during or immediately following some copulations. In this study, we determined which of several variables associated with copulation correlated with paternity success in P. globosus when two males mate with a single female. Then, by determining which of these variables also correlated with sperm dumping, we inferred which variables may affect paternity via the mechanism of sperm dumping. Male abdomen vibration (a copulatory courtship behaviour) and male genitalic squeezing both correlated with both paternity and sperm dumping; so, these traits may be favoured by biased sperm dumping. Biased sperm dumping may also be the mechanism by which possible cryptic female choice favours another male trait that was the subject of a previous study, responsiveness to female stridulation. © 2009 European Society For Evolutionary Biology.